PENERAPAN ALGORITMA FP GROWTH PADA PENJUALAN PRODUK DISTRO RADEN MADURA - Putra, Arya Kamandanu; Hamonangan, Ryan; Herdiana, Ruli; Tohidi, Edi; Hayati, Umi (LPPM UNIKA Santo Thomas Medan, 2022)
The transaction data for the purchase of the distro's cost of selling is quite stable but its sales are less than the sales target, so it is necessary to manage sales data. The focus of this research is focused on the management of purchase transaction data that will be used as a dataset. The management uses the FP-Growth algorithm which takes from the item set, from the algorithm it gets a buying pattern that will become information for making a decision. Based on the results of the study, the authors conclude that the pattern of purchases by consumers gets a pattern of sales, namely, consumers by buying 1 item of T-shirts from distributions will buy back one item of T-shirts from 26 different distributions. consumers by buying 2 items of t-shirts distributions will buy back 1 item of t-shirts from different distributions as many as 72 patterns, and consumers by buying 3 items of t-shirts distributions will buy back 1 item of t-shirts with different distributions of 25 patterns.